IMPLEMENTASI PENDEKATAN DEEP LEARNING BERBASIS NASKAH TULAK-TULAK PADA MATERI SIKLUS HIDUP HEWAN SEBAGAI UPAYA DIGITALISASI BUDAYA - Jalilah Azizah Lubis; Ananda Siddiq; Ilmi Aulina Rahim; Tiara Angraini Hasibuan; Sutan Muda (Postgraduate, University of Mataram, 2026)
Local wisdom education can preserve traditional scripts (such as Tulak-Tulak) which are threatened with extinction by incorporating them into learning. This study aims to improve students' understanding of the Animal Life Cycle material through the application of a deep learning approach based on the Tulak-Tulak script as an effort to digitize and preserve Mandailing culture. The study was conducted at SD Negeri 150 Tano Bato, Mandailing Natal Regency, with 22 fourth-grade students as subjects. The method used was classroom action research (CAR) consisting of two cycles, each consisting of the planning, action, observation, and reflection stages. Data were collected through observation, interviews, and written tests. The results of the study showed a significant increase in student learning outcomes, with the percentage of completion increasing from 23.8% in Cycle I to 90.9% in Cycle II. The application of a deep learning approach based on meaningful, mindful, and joyful learning has been proven to improve students' conceptual understanding and foster higher learning interest. The integration of the Tulak-Tulak script in learning not only provides a contextual and interactive learning experience, but also introduces and preserves local cultural values ​​through the science learning process. Thus, the implementation of the Tulak-Tulak script-based deep learning approach is an effective innovation in improving the quality of learning while strengthening efforts to digitize regional cultural heritage in elementary education environments.